Building Large-Scale Web Applications with Angular : Your one-stop guide to building scalable and production-grade Angular web apps /: Your one-stop guide to building scalable and production-grade Angular web apps. (2018) - Arora, Chandermani; Hennessy, Kevin; Noring, Christoffer; Uluca, Doguhan
No abstract available